2017
DOI: 10.1177/1535370216689828
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antibacterial effects of herbal extracts and antibiotics on methicillin-resistant Staphylococcus aureus: A computational and experimental study

Abstract: Antibiotic resistant is a well-known threat to global health and methicillin-resistant Staphylococcus aureus is one of the most significant ones. These resistant bacteria kill thousands of people every year and therefore a new effective antimicrobial treatment is necessary. This study identified the herbs and their associated bioactive ingredients that can potential the effects of current antibiotics. These herbs have long history of human usage in China and have well-defined monograph in the Chinese Pharmacop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 63 publications
4
47
0
3
Order By: Relevance
“…The outcomes showed that the addition of 64 μg/mL of tiliroside may lower the MIC of tested antibiotics by 2 (ofloxacin) to 128 (acriflavine) times (Falcão‐Silva, Silva, Souza, & Siqueira‐Junior, ). As was observed in computational studies, tiliroside can presumably also inhibit penicillin‐binding proteins 2a (PBP2a) and 4 (PBP4), produced by methicillin‐resistant S. aureus (Kuok et al., ) The drug resistance of various microorganisms was apparent from the beginning of antibiotic development. However, the disturbing and dangerous appearance of rising numbers of resistant bacteria has recently been noted (Fair & Tor, ).…”
Section: Biological Activities Of Tilirosidementioning
confidence: 94%
“…The outcomes showed that the addition of 64 μg/mL of tiliroside may lower the MIC of tested antibiotics by 2 (ofloxacin) to 128 (acriflavine) times (Falcão‐Silva, Silva, Souza, & Siqueira‐Junior, ). As was observed in computational studies, tiliroside can presumably also inhibit penicillin‐binding proteins 2a (PBP2a) and 4 (PBP4), produced by methicillin‐resistant S. aureus (Kuok et al., ) The drug resistance of various microorganisms was apparent from the beginning of antibiotic development. However, the disturbing and dangerous appearance of rising numbers of resistant bacteria has recently been noted (Fair & Tor, ).…”
Section: Biological Activities Of Tilirosidementioning
confidence: 94%
“…For example, Staphylococcus aureus, one of the most dangerous human pathogens, causing a wide range of infections from mild skin diseases to life-threatening endocarditis [23,84]. The greatest problem is the methicillin-resistant (MRSA) S. aureus strain, which is the fastest-evolving pathogen in the last decade and one of the most common causes of multidrug-resistant infections with significant morbidity and mortality, especially in developing countries [85]. After identifying methicillin-resistant strains, vancomycin and quinolones antibiotics have been used as alternative drugs of choice in staphylococcal infections therapy [86].…”
Section: Antimicrobial Properties Of Smops: the Reserve Players Againmentioning
confidence: 99%
“…Both PBP2a protein and mecA gene are emerging antimicrobial targets for therapeutics development [159,160]. Various type of natural products targeting mecA gene or PBP2a have also been reported, these compounds include curcumin [161], tiliroside, pinoresinol, magnatriol B, and momorcharaside B [151], Acalypha wilkesiana (evergreen shrub) extract [136], and Poncirus trifoliata extract [139]. In combination with antibiotics, several natural compounds have also reduced the expression of PBP2a.…”
Section: Penicillin-binding Protein 2a (Pbp2a)mentioning
confidence: 99%